Meningkatkan Aktivitas dan Hasil Belajar Ipa Biologi Melalui Penerapan Model Kooperatif Tipe Team Games Tournament (TGT) Pada Siswa Kelas VIII F di SMP Negeri 1 Barombong Kabupaten Gowa - Qurniasty Qurniasty; Firdaus Daud; Halifah Pagarra (UNM Journal of Biological Education, 2018)
This research is a classroom action research conducted for two cycles. The purpose of this study to increase the activity and learning outcomes of learners through the application of cooperative model of team games tournament type. The subjects of the study were students of class VIII F in the junior high school 1 Barombong Gowa district. Data collection was conducted in the even semester of the academic year 2017/2018. Research data collected there are two activities and learning outcomes of learners. Student learning activities are collected during the learning process which is observed by two observers by using observation sheet, then the learning result data is obtained through the evaluation test which is done at the third meeting at the end of the cycle, the final test of the given cycle is a matter of multiple choice as much as 20 twenty) items. All data obtained were analyzed in two ways, namely qualitative analysis for learners 'and quantitative learning activities for learners' learning outcomes. Results of research on learning activities of students showed the average on the first cycle of 65.55%, while in the second cycle of 84.43%. Through quantitative analysis, it is known to the students' completeness category where the total percentage of learners who completed in the first cycle is 60%, while in the second cycle reaches 80%. So it can be concluded that the application of cooperative model of team tournament type of team can improve the activity and learning outcomes of learners.